Experimental and theoretical studies of milk and air motion in the milk-producing tract of the milking machine - A. A. Rylov; P. A. Savinykh; V. N. Shulyatyev (Аграрная наука Евро-Северо-Востока)
The article provides a theoretical analysis of the process of milk movement from the milk chamber of the collector through the milk hose to the milk pipeline using a continuous model of the plug flow of a two-phase medium. There have been obtained analytic expressions that allow determining the values of pressure drop in the descending and ascending sections of the milk hose. According to the results of the theoretical analysis for two-stroke milking machine of pairwise action there was obtained a linear dependence (R2=0.9965) between the pressure drop in the milk hose and intensity of milk production. Experimental studies of the value of the pressure drop in the milk hose of the milking machine performed in a cowshed for 200 heads of one of the leading enterprises of the Kirov region confirmed a very close relationship (R2 = 0.9967) between the current intensity of milk production and the pressure drop in the milk hose when the milk-air mixture moves. Over the entire range of variation in the intensity of lactation, the pressure loss in the descending section varies in the range Δртр12 = 0.85…1.47 Pa. According to the absolute contribution to the total pressure loss Δр1-3 = 8293.80…12705.32 Pa, the pressure loss for overcoming gravity force in the ascending section of the milk hose Δргр = 6611.31…10992.27 Pa has the greatest influence. The results of calculations of the pressure drop in the milk hose performed according to the algorithm proposed in the article, fit into the confidence interval of the experimental measurement of the pressure drop with a 5% significance level. Using the results of the research will allow to predict pressure losses in the milk hose in dependence to the intensity of milk production and take into account the results of calculations when designing milking machines and developing their functioning algorithms for milking high-yield cows.